Two-Dimensional Ferroelectric Materials: From Prediction to Applications - Shujuan Jiang; Yongwei Wang; Guangping Zheng (Nanomaterials)
Ferroelectric materials hold immense potential for diverse applications in sensors, actuators, memory storage, and microelectronics. The discovery of two-dimensional (2D) ferroelectrics, particularly ultrathin compounds with stable crystal structure and room-temperature ferroelectricity, has led to significant advancements in the field. However, challenges such as depolarization effects, low Curie temperature, and high energy barriers for polarization reversal remain in the development of 2D ferroelectrics with high performance. In this review, recent progress in the discovery and design of 2D ferroelectric materials is discussed, focusing on their properties, underlying mechanisms, and applications. Based on the work discussed in this review, we look ahead to theoretical prediction for 2D ferroelectric materials and their potential applications, such as the application in nonlinear optics. The progress in theoretical and experimental research could lead to the discovery and design of next-generation nanoelectronic and optoelectronic devices, facilitating the applications of 2D ferroelectric materials in emerging advanced technologies.